FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR OLEH IBU POST OP SECTIO CAESAREA DI RS PMC KOTA PEKANBARU - Elfiza Fitriami, Reny Afwinasyah (Jurnal Ilmiah Keperawatan, 2021)
Background: Early administration of colostrum to newborns is the best protection. Several things can affect the success of giving colostrum in the first hour of birth, for example for women with Caesarean section. Some women with Caesarean section do not agree to give it on the first day, even though they know about the importance of breastfeeding. The most important factor affecting mothers in giving colostrum to babies is the level of knowledge. In addition, the mother's education level has an influence in giving colostrum. Family support is also an external factor that has the greatest influence on the success of giving colostrum. Purpose: to determine the factors that are associated with the provision of colostrum to newborns by post-op sectio caesarean mothers. Methods: This type of research is quantitative, using cross-sectional, the sample in this study is 30 post-op caesarean mothers. Results: data obtained that there is a relationship between the level of maternal education and the provision of colostrum to post-op caesarean mothers (p: 0.010), there is a relationship between the level of maternal knowledge and the provision of colostrum to post-op caesarean mothers (p = 0.006), there is a relationship between family support and provision colostrum in post-op caesarean mothers (p: 0.02). Conclusion: there is a significant relationship between education level, knowledge level and family support for colostrum administration in newborns by post-op sectio caesarean mothers